Kebijakan Belanja Negara dalam Tinjauan Fikih - Ibrahim, Yusriadi; Zulhamdi, Zulhamdi (Department of Islamic Economic Law, Faculty of Sharia, Sultanah Nahrasiyah State Islamic University, Lhokseumawe, 2023)
Islam is a perfect teaching that includes learning norms for human life in the world and the hereafter, including economic learning which includes the State's shopping policy as one of the fiscal tools of the State, all of which have a purpose for the welfare of individuals and society. In this paper, the author will try to collect data from several literatures to examine briefly how Islam and economics as well as the State expenditure policy based on Islam, in terms of understanding, history, its application in modern times, as well as its combination with existing conventional system or which has been applied in advance by States which sometimes cause obstacles and problems in its implementation. Islam is a perfect teaching that includes learning norms for human life in the world and the hereafter, including economic learning which includes the State's shopping policy as one of the fiscal tools of the State, all of which have a purpose for the welfare of individuals and society. In this paper, the author will try to collect data from several literatures to examine briefly how Islam and economics as well as the State expenditure policy based on Islam, in terms of understanding, history, its application in modern times, as well as its combination with existing conventional system or which has been applied in advance by States which sometimes cause obstacles and problems in its implementation.